Do Poor Economic Conditions Affect Terrorism? - Claude Berrebi; Esteban F. Klor (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
While the existing empirical literature shows that poverty and economic conditions are not correlated with the quantity of terror, theory predicts that poverty and poor economic conditions may affect the quality of terror. Poor economic conditions may lead more able individuals to participate in terror attacks, allowing terror organizations to send betterqualified terrorists to more complex, high-impact terror missions. Using data on Palestinian suicideterrorists, we provide evidence of the correlation between economic conditions, the characteristics of suicide terrorists, and the targets they attack.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330